2000
DOI: 10.1046/j.1523-1755.2000.00284.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of current smoking and smoking discontinuation on renal function and proteinuria in the general population

Abstract: In the general population, smokers do not exhibit lower creatinine clearance than never smokers. In fact, creatinine clearance is slightly higher in current smokers at least in men, even when normotensive and hypertensive subjects are analyzed separately, but the difference is small, especially in women. This effect seems reversible upon smoking discontinuation. Chronic smoking results in a marked risk of irreversible proteinuria that may occur despite moderate smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
99
3
5

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 35 publications
12
99
3
5
Order By: Relevance
“…Halimi et al 7 reported a high Ccr or large glomerular filtration rate (GFR) in smokers in a general French population, similar to our findings. Briganti et al, 8 however, reported a decrease in Ccr related to lifelong accumulated cigarette consumption.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Halimi et al 7 reported a high Ccr or large glomerular filtration rate (GFR) in smokers in a general French population, similar to our findings. Briganti et al, 8 however, reported a decrease in Ccr related to lifelong accumulated cigarette consumption.…”
supporting
confidence: 91%
“…Nicotine causes constant renal vasodilatation by release of nitric oxide and natriuretic peptides, with the repeated renal vasodilatations causing chronic glomerular hyperfiltration. 7 Or, transient renal hypoperfusion is caused by each cigarette use, and the repeated hypoperfusion may damage some glomeruli, and this in turn induces hyperfiltration in the remnant glomeruli. Normal or high GFR in smokers hence reflects a compensated phase, but which would eventually deteriorate to the renal failure phase.…”
mentioning
confidence: 99%
“…In a cross-sectional study from France, smoking was not associated with decreased creatinine clearance (40). By contrast, a cross-sectional study from Australia (41) found that smoking was independently associated with renal impairment and proteinuria.…”
Section: Discussionmentioning
confidence: 85%
“…After adjustment for potential confounding factors, current smokers who smoked Ͻ20 or Ͼ20 cigarettes per day, respectively, had an elevated risk for high-normal urine albumin concentration (relative risk [RR] 1.33 and 1.98, respectively). Halimi et al (16) studied 28,409 volunteers from the general population. They found that current and former smokers had a marked risk for macroalbuminuria (adjusted RR 3.26 and 2.69, respectively), indicating nonreversible kidney damage related to smoking.…”
Section: General Populationmentioning
confidence: 99%